2016
DOI: 10.1111/ecc.12598
|View full text |Cite
|
Sign up to set email alerts
|

Assessing psychological and supportive care needs in glioma patients - feasibility study on the use of the Supportive Care Needs Survey Short Form (SCNS-SF34-G) and the Supportive Care Needs Survey Screening Tool (SCNS-ST9) in clinical practice

Abstract: Neuro-oncological patients experience high symptom and psychosocial burden. The aim was to test feasibility and practicability of the Supportive Care Needs Survey Short Form (SCNS-SF34-G) and the SCNS-Screening Tool (SCNS-ST9) to assess supportive care needs of neuro-oncological patients in clinical routine. A total of 173 patients, most with a primary diagnosis of high-grade glioma (81%), were assessed first using SCNS-SF34-G in comparison to two well-established patient-reported outcome measures, the Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 53 publications
(96 reference statements)
0
33
0
Order By: Relevance
“…In clinical trials for brain cancer patients, QOL form completion can be poor, with either no form completed or missing items (Dirven et al, 2014;Walker et al, 2003). A recent study in Germany with patients diagnosed with glioma highlighted that even with support in clinics up to 10% of participants erroneously completed the SCNS-34 and this rises to 20% without support (Renovanz et al, 2016). They highlighted structure and comprehension as contributing factors but also noted that if patients were distressed more errors occurred.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials for brain cancer patients, QOL form completion can be poor, with either no form completed or missing items (Dirven et al, 2014;Walker et al, 2003). A recent study in Germany with patients diagnosed with glioma highlighted that even with support in clinics up to 10% of participants erroneously completed the SCNS-34 and this rises to 20% without support (Renovanz et al, 2016). They highlighted structure and comprehension as contributing factors but also noted that if patients were distressed more errors occurred.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted several observational studies before that led to the research question of the GLIOPT trial. Hereby we found that 1) some questionnaires do not fit to the requirements of HGG patients (6,11), 2) patients in reduced clinical condition with high unmet needs may be missed by a questionnaire or tablet assessment (8,12) and 3) we can use "signaling items" probably indicating patients in need of support (13). Applying these items in a face-to-face conversation of doctor and patient was possible.…”
Section: Preliminary Workmentioning
confidence: 95%
“…We conducted several observational studies before that led to the research question of the GLIOPT trial. Hereby we found that 1) some questionnaires do not fit to the requirements of HGG patients (6,11), 2) patients in reduced clinical condition with high unmet needs may be missed by a questionnaire or tablet assessment (8,12) and 3) we can use "signaling items" probably indicating patients in need of support (13). Applying these items in a face-to-face conversation of doctor and patient was possible.…”
Section: Preliminary Workmentioning
confidence: 96%
“…However, screening instruments have been rarely adapted to the diverse needs of neuro-oncological patients so far (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation